2010
DOI: 10.1128/jvi.00159-10
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Pandemic H1N1 Influenza Viruses in Mice

Abstract: The molecular mechanism by which pandemic 2009 influenza A viruses were able to sufficiently adapt to humans is largely unknown. Subsequent human infections with novel H1N1 influenza viruses prompted an investigation of the molecular determinants of the host range and pathogenicity of pandemic influenza viruses in mammals. To address this problem, we assessed the genetic basis for increased virulence of A/CA/04/09 (H1N1) and A/TN/1-560/09 (H1N1) isolates, which are not lethal for mice, in a new mammalian host … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
205
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(218 citation statements)
references
References 58 publications
11
205
1
1
Order By: Relevance
“…Reassortment experiments with 2009 H1N1 isolates have also shown that PA is important for the polymerase activity and virulence of A/California/04/2009 in mice, providing further evidence for a crucial role of the PA subunit (33,43). Finally, mutations in PA that arose during the creation of a highly pathogenic 2009 pH1N1 variant created by serial passage in mice contributed to enhanced polymerase function and, potentially, the highly pathogenic phenotype (18). Whether PA T552 in 2009 pH1N1 viruses will mutate to S552, or if this change increases polymerase activity in 2009 pH1N1, remains to be determined, although this mutation has not arisen during multiple adaptation experiments (18,53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reassortment experiments with 2009 H1N1 isolates have also shown that PA is important for the polymerase activity and virulence of A/California/04/2009 in mice, providing further evidence for a crucial role of the PA subunit (33,43). Finally, mutations in PA that arose during the creation of a highly pathogenic 2009 pH1N1 variant created by serial passage in mice contributed to enhanced polymerase function and, potentially, the highly pathogenic phenotype (18). Whether PA T552 in 2009 pH1N1 viruses will mutate to S552, or if this change increases polymerase activity in 2009 pH1N1, remains to be determined, although this mutation has not arisen during multiple adaptation experiments (18,53).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, mutations in PA that arose during the creation of a highly pathogenic 2009 pH1N1 variant created by serial passage in mice contributed to enhanced polymerase function and, potentially, the highly pathogenic phenotype (18). Whether PA T552 in 2009 pH1N1 viruses will mutate to S552, or if this change increases polymerase activity in 2009 pH1N1, remains to be determined, although this mutation has not arisen during multiple adaptation experiments (18,53).…”
Section: Discussionmentioning
confidence: 99%
“…The progeny viruses carried K119N, G155E, S183P, R221K, or D222G hemagglutinin protein mutations and were more virulent than the unpassaged A(H1N1)pdm09 virus. 54 The implications of this study for pathogenesis of the virus in other mammals remains unknown, even though D222G has been associated with increased virulence in humans. [42][43][44][45] However, a reverse genetics hemagglutinin protein D222G A(H1N1)pdm09 mutant was generated and inoculated into ferrets without any increase in virulence.…”
Section: Molecular Markers Of Virulencementioning
confidence: 99%
“…These mutations occurred upon serial passage in mice and were shown to be responsible for enhanced transcription and replication of the virus. 54,61 Nonstructural protein 1 is another influenza protein well known to be involved in virulence. A(H1N1)pdm09 viruses possess a truncated nonstructural protein 1 of 220 amino acids.…”
Section: Molecular Markers Of Virulencementioning
confidence: 99%
“…Furthermore, PA-P149S, R266H, L357I, and T515S have been reported to increase the polymerase activity of H5N1 viruses in 293T cells (20). Many PA amino acid mutations in H1 and H7 subtype viruses also contribute to overcoming host species barriers (17,(22)(23)(24)(25)(26)(27)(28).…”
mentioning
confidence: 99%